An Algorithm to Define Emotions Based on Facial Gestures as Automated Input in Survey Instrument - Tayib, Saifulazmi; Jamaludin, Zulikha (American Scientific Publishers, 2016)
This study is carried out to help researchers who are having problem in acquiring accurate responses or answers from dyslexic children in their survey instrument.Due to the children impairment in reading, spelling and writing, researchers who conduct studies on this particular group are unable to gather valuable information from their subjects.Therefore, this paper examines on the use of facial gestures as input in survey instrument. Features of facial gestures that play important role in creating emotions are selected to be formulated in the algorithm.The aim of this paper is to produce an algorithm to define emotions based on three facial features namely mouth, eyes, and eyebrows.This is done by studying users and the problem domain, analyzing the relationship between emotions and facial gestures, and formulating solutions to the problem.This algorithm will be useful in developing a more interactive survey instrument and improving user interaction between researchers and dyslexic children.